Altered epigenetic pathways and cell cycle dysregulation in healthy appearing skin of patients with koebnerized squamous cell carcinomas following skin surgery. (13th March 2018) - Gambichler, T.; Rüddel, I.; Hessam, S.; Bechara, F.G.; Stockfleth, E.; Schmitz, L.
Abstract: Background: Koebnerized non‐melanoma skin cancer following skin trauma represents a rare and obscure event. Objectives: To study molecular pathological parameters in koebnerized squamous cell carcinomas (K‐SCCs) occurring after complete tumour removal. Methods: We assessed two patients with multiple sclerosis who were on treatment with dimethylfumarate (DMF) preceded by long‐term azathioprine therapy. Both patients rapidly developed several K‐SCCs following histopathologically proven complete excision of cutaneous SCCs. We performed immunohistochemistry for p53, p16, Ki‐67, TET‐2, IDH‐2, 5‐hmc and 5‐mc. PCR was carried out for the detection of human papilloma viruses. Mutation analysis was performed for BRAF, K‐RAS and EGFR. Results: All lesions investigated were negative for HPV DNA. Mutations were not detected. Healthy appearing skin of both patients showed relatively high Ki‐67, p16 and p53 expression which was comparable to the expression observed in primary SCCs as well as K‐SCCs. Protein expression of Ki‐67, p16 and mutant p53 was barely detected in the specimens of the healthy controls. A decreased protein expression of TET‐2 enzyme was seen in all tumours and healthy appearing skin when compared to the skin of healthy controls. Conclusions: We observed two patients with K‐SCCs developing under DMF treatment. In healthy appearing skin of patients with K‐SCCs, wound healing processes, including induction of proliferation and growth factor release, might promote the growth of preneoplastic keratinocytes and cancer formation on the basis of pre‐existing altered epigenetic pathways and cell cycle dysregulation. Although fumarates can reduce TET‐2 expression, the role of DMF intake in the development of K‐SCCs remains unclear.